Innovation in Hydraulic Fracturing Technology Using Ctafs in Production Optimization Strategy in Unconventional Reservoir Barnett Shale: A Geology and Rock Physics Based Approach - Pratama, Fauzan Abiyyu; Nugraha, Fanata Yudha; Baiti, Aisah Nur; Damayanti, Nabila Zafira (Journal of Earth Energy Science, Engineering, and Technology, 2025)
The Barnett Shale is the largest unconventional hydrocarbon-producing rock formation in the United States. It consists of shale rocks with high-density mineral content such as smectite, silica, and carbonate, which result in low permeability and porosity. Hydraulic fracturing utilizing the coiled tubing activated frac sleeve completion system (CTAFS) is employed to enhance hydrocarbon production by fracturing the formation. The application of hydraulic fracturing can significantly boost production from the Barnett Shale. To optimize this method, geological analysis and rock physics properties are essential to derive parameters such as predictions of Young’s modulus and Poisson’s ratio in the exploration area. This study uses a systematic review approach based on previous research, supported by secondary data instrumentation including rock core validation and well data digitization, which are subsequently modeled into rock physics parameters. The rock physics model is used to simulate the elastic properties of the rock formation, considering the matrix, constituent composition, and rock heterogeneity. Furthermore, hydraulic fracturing simulations are conducted to predict production and determine the resulting strategies. The research findings indicate that in the interval 10,650–10,725 ft of the EnerGeo1 well, kerogen volumetrics are 18%, quartz 38%, clay 35%, and calcite 15%. The Young’s modulus value is 39.5 GPa, and the Poisson’s ratio is 25.2%, categorizing it as Type 1. In the interval 10,725–10,803 ft, kerogen volumetrics are 18%, quartz 32%, clay 41%, and calcite 16%. The Young’s modulus value is 37.1 GPa, and the Poisson’s ratio is 24.8%, categorizing it as Type 2. In the interval 10,803–10,880 ft, kerogen volumetrics are 19.6%, quartz 41%, clay 31%, and calcite 11%. The Young’s modulus value is 43.3 GPa, and the Poisson’s ratio is 26.6%, categorizing it as Type 3. The data reveals that Type 3 rocks are more suitable for hydraulic fracturing compared to Type 1. Meanwhile, Type 2 rocks are identified as being suitable for placing horizontal wells due to the clay and calcite matrix, which can prevent formation collapse. It can be concluded that integrating geological and rock physics data can yield a more efficient and innovative fracturing design, resulting in a production increase of up to 129% compared to previous production levels.